The Limited Impact of Running Performance on Football Success in the Turkish Super League - Spyridon Plakias; Sotiris Tasoulis; Angelos E. Kyranoudis; Christos Kokkotis; Serafeim Moustakidis (Applied Sciences)
Given that performance in football depends on tactical, technical, physical, and mental skills, the purpose of this study was to investigate whether there are differences in running performance between winning and non-winning teams in the Turkish League, taking into account the influence of game location and the comparative quality of the team and its opponents. Utilizing a dataset from the 2021–2022 season provided by InStat Fitness, an optical tracking technology platform certified by FIFA, the analysis included 185 matches after adjusting for matches with red card incidents. The research employed both two-way ANCOVA and binary logistic regression analyses to explore the relationships between running performance (categorized into four intensity zones) and match results, considering factors such as match location and teams’ strength. The results of the two-way ANCOVAs indicate that running performance metrics, specifically the distances covered at different intensities, even in cases where statistically significant differences are observed, have small practical significance (partial eta squared ≤ 0.03 in all cases). Conversely, as shown by the binary logistic regression, home advantage triples the probability of winning (p < 0.001, Exp(B) = 3.119), while the increase in probability caused by team quality (p < 0.001, Exp(B) = 1.085) and the decrease caused by opponent quality (p < 0.001, Exp(B) = 0.911) are also significant. The conclusions highlight that running performance metrics are not decisive predictors of match outcomes in professional football. This suggests the importance of integrating tactical, technical, and psychological factors into team preparation and performance analysis. This study underscores the need for future research to adopt dynamic methods that reflect the game’s fluid nature and to explore these relationships across various leagues and seasons to enhance the generalizability of the findings.